Artificial Intelligence in Solar Energy Applications - Kalogirou, Soteris A. (My University, 2001)
Artificial intelligence (AI) systems comprise two major areas, expert systems and artificial neural networks (ANNs). The major objective of this paper is to illustrate how artificial intelligence techniques might play an important role in modelling and prediction of the performance of solar energy systems. The paper outlines an understanding of how expert systems and neural networks operate by way of presenting a number of problems in the different disciplines of solar energy engineering. The various applications of expert systems and neural networks are presented in a thematic rather than a chronological or any other order. Results presented in this paper, are testimony to the potential of artificial intelligence as a design tool in many areas of solar energy engineering.
Keywords: Expert systems; Artificial Neural Networks (ANN); Renewable energy applications